Pelvic Plexus Block Versus Periprostatic Nerve Block for Ultrasound-Guided Prostate Biopsy: A Meta-Analysis - Ding, Hui; Ning, Zhongyun; Ma, Hongwu (Frontiers in Oncology, 2021)
Background: To relieve prostate biopsy-related pain, various local anesthetic methods have been used.The best approach was periprostatic nerve block (PNB) in the past decade. Recently, pelvic plexus block (PPB) was employed to ultrasound-guided prostate biopsy. Compared with the PNB, the PPB may block a more extensive area. Therefore, PPB may be more effective in relieving prostate biopsy-related pain. However, several prospective randomized controlled trials (RCTs) comparing PPB and PNB drew conflicting conclusions, so we compared the difference of pain control between PPB and PNB for prostate biopsy. Methods: The following database were retrieved up to October 2020: PubMed, Chinese biomedicine literature database, the Cochrane Library, China National Knowledge Internet databases, Wanfang databases and Google Scholar. Only the randomised controlled trials (RCTs) were included. The main outcome measures were Visual Analogue Scale(VAS) score and complications. The literature quality and extracted data were evaluated by two authors independently. The software Review Manager(version 5.3) was used to perform the data analysis that comparing the difference of VAS score and complications between PPB and PNB. Results: After screening, six articles including 336 patients from PPB group and 337 patients from PNB group were performed meta-analysis in this study. The results showed that there were no significant difference of pain control in probe insertion and local anesthetic injection between PPB and PNB, while compared with PNB, patients with PPB experienced less pain during biopsy and 30 min after biopsy, respectively(MD=-0.57, 95% CI: -1.11－-0.03, Z=2.06, P=0.04; MD=-0.21, 95% CI: -0.40－-0.02, Z=2.15, P=0.03). In subgroup analysis, the pooled results showed that PPB was superior to PNB in 12-cores biopsy (pooled MD=-1.16, 95% CI: -1.61－-0.71, P˂0.00001), and more than 40ml prostate size, regardless of transrectal or transperineal prostate biopsy. The reported major complications were urinary retention, hematuria, infection and hemospermia. The pooled results showed that there were no obvious difference in complications between PPB group and PNB group. Conclusions: Overall, this meta-analysis suggests that PPB provides safe and effective pain control of ultrasound-guided prostate biopsy, and PPB is superior to PNB. In future, it also needs more high quality, large samples RCTs to verify.